Role of Cannabinoid Receptors in Crocin﻿-Induced Hypoalgesia in Neuropathic Pain in Rats - Vafaei, Abbas Ali (J Exp Pharmacol, 2020)
PURPOSE: Neuropathic pain involves injury or alteration of the normal sensory and modulatory nervous systems to produce a set of symptoms that are often difficult to treat. Previous study indicates that crocin has anti-inflammatory properties that may be mediated by the neurotransmitter system. In this study, we determine if there is an interaction between crocin and the cannabinoid system on ﻿chronic ﻿constriction ﻿injury (CCI)﻿-induced neuropathic pain in male rats. MATERIALS AND METHODS: In this experimental study, adult male Wistar rats (220–250 g) were used. CCI was induced by setting four loose ligatures around the ﻿sciatic nerve. In part 1, after nerve lesion, vehicle, ﻿crocin (60 mg/kg) or Win 55-212-2 (0.1 mg/kg) as an agonist and AM 251 (0.1 mg/kg) as an antagonist of cannabinoid receptors were injected intraperitoneally daily in separate groups for 2 weeks. In part 2, two weeks after nerve lesion, vehicle (5 µL), crocin (6 µg/5 µL), Win 55-212-2 (0.1 µg/5 µL), AM 251 (0.1 µg/5 µL) were administered intracerebroventricularly (ICV) in separate groups. Mechanical allodynia and thermal hyperalgesia were measured using Von Frey filaments and plantar test device, respectively, at day 14. Data were analyzed by ﻿two-way ANOVA and Sidak’s multiple comparisons post-test. RESULTS: Results indicated that centrally administered crocin significantly decreased thermal hyperalgesia and mechanical allodynia. Also, peripheral injection of ﻿crocin significantly decreased mechanical allodynia but not thermal hyperalgesia. Central or peripheral administration of Win 55-212-2 or AM 251 modulates the analgesic effect of ﻿crocin significantly. CONCLUSION: Our findings showed that ﻿crocin ﻿has significant analgesic effects that are probably mediated by an endocannabinoid mechanism.